2020
DOI: 10.1136/bcr-2020-235378
|View full text |Cite
|
Sign up to set email alerts
|

Titinopathy, an atypical respiratory failure

Abstract: Hereditary myopathy with early respiratory failure is a neuromuscular disease with an autosomal dominant inheritance pattern. Clinical presentation is characterised by proximal and distal muscle weakness, exertional dyspnoea and generalised fatigue. There is no disease-modifying therapy and the prognosis is unknown. Herein we present a case of a 40-year-old woman with long-standing asthenia and apathy and, more recently, daytime sleepiness, dyspnoea and difficulty in walking. A hypercapnic respiratory failure … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 10 publications
2
4
0
Order By: Relevance
“…On biopsy, more than 80% patients had cytoplasmic bodies. [13][14][15] In our study, the clinicopathological features of patients 1 and 2 were consistent with those in previous reports. However, patient 1 showed initial symptoms at age 15 years, suggesting that mutations in exon 344 of TTN is considered a cause of muscle weakness in teenage patients with myopathy.…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…On biopsy, more than 80% patients had cytoplasmic bodies. [13][14][15] In our study, the clinicopathological features of patients 1 and 2 were consistent with those in previous reports. However, patient 1 showed initial symptoms at age 15 years, suggesting that mutations in exon 344 of TTN is considered a cause of muscle weakness in teenage patients with myopathy.…”
Section: Discussionsupporting
confidence: 92%
“…In previous reports, all the patients with these two mutations had an adult onset (after 20 years of age), and showed muscle weakness and respiratory disturbance. On biopsy, more than 80% patients had cytoplasmic bodies 13–15 . In our study, the clinicopathological features of patients 1 and 2 were consistent with those in previous reports.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…It was first found to co‐segregate with the disease in the 3 unrelated Swedish families tested (Ohlsson et al, 2012); another study, published separately but almost concomitantly, found the same variant in 3 British families, again co‐segregating with observed pathology (Pfeffer et al, 2012). It has subsequently been reported in a number of studies, in different ethnic groups: in individuals of British, Swedish, Finnish, Italian, and Argentinian ancestry (Palmio et al, 2014); in two individuals, one of Native Canadian and one of Spanish ancestry (Toro et al, 2013), with the distinct ancestral haplotype of the Native Canadian patient suggesting independent origins in different ethnic groups; in two separate studies of myofibrillar myopathy (MFM), associated with HMERF pathology related to that condition (Pfeffer et al, 2014; Uruha et al, 2015); in a Chinese family in 2015 (Yue et al, 2015), confirming this variant as having a worldwide distribution; in one individual in a British cohort for a study of clinical applications of magnetic resonance imaging (MRI) (Bugiardini et al, 2018); in one Afghan, one Spanish, and two unrelated Italian individuals, as well as four individuals in a family of Russian ancestry (Palmio et al, 2019); in a Portuguese patient (Morais et al, 2020); in a Chinese patient (Huang et al, 2021). Finally, the variant domain has been experimentally characterized in vitro, and was found to greatly decrease the solubility and folding of the Fn3‐119 domain, where the wild‐type domain and those with common variants did not (Hedberg, Toledo, et al, 2014).…”
Section: Variant Impact By Sarcomere Regionmentioning
confidence: 87%